Analisis Cluster K-Means dengan Metode Elbow untuk Menentukan Pola Penjualan Produk Traffic Room Summarecon Mal Bekasi - Prasetya, Ajie; Salkiawati , Ratna; Alexander , Allan D (Journal of Students‘ Research in Computer Science, 2023)
An effective sales strategy in the fashion retail business is essential to determine the success of the company or store. Like the Traffic Room store, which is a vintage fashion retail store that sells a variety of products. Although there are many products on sale, this store has not utilized sales data to determine product sales patterns, causing negative impacts such as there are still many products that are in short supply and products are not sold with predetermined targets. So the purpose of this study is t o determine product sales patterns in order to improve product inventory. To solve this problem, the analysis used is the K-Means algorithm to find product sales patterns assisted by the elbow method in determining the optimal cluster. As well as the flow in this research process is the CRISP-DM method with steps namely business understanding, data understanding, data preparation, modeling, evaluation and deployment. The results of this study obtained 4 clusters, namely cluster 2 or very in demand there are 2 products, cluster 3 or in demand there are 5 products, cluster 1 or quite in demand there are 5 products and cluster 4 or less in demand there are 3 products. The evaluation results get the optimal Sum of Square Error (SSE) value of 594,366.733 or 65.5%. From the evaluation results, it means that the performance of the K-Means algorithm used is good.